Rapid analysis and identification of multi-class mycotoxins in Morinda officinalis by UFLC-ESI-MS/MS. Issue 78 (26th August 2015) - Liu, Hongmei; Kong, Weijun; Liu, Congmin; Liu, Qiutao; Hu, Yichen; Yang, Meihua
<x xml:space="preserve">Abstract</x> Simultaneous quantification and identification of multi-class mycotoxins in Morinda officinalis by DAS-UFLC-MS/MS.